Space division multiplexing in multimode fiber for channel diversity in data communications - Amphawan, Angela; Fazea, Yousef; Elshaikh, Mohamed (Springer International Publishing, 2015)
Space division multiplexing (SDM) has recently gained eminence as a means to alleviate data traffic congestion to future-proof current network infrastructure. This paper reports on SDM of a new spiral-phased wave front comprising modified Laguerre-Gaussian (LG) and Hermite-Gaussian (HG) modes on a wavelength of 1550.12 nm over a 2 km-long MMF. Power coupling coefficients, degenerate mode group delays and bit-error rates are analyzed for different vortex orders.